APPLICATION OF 3D TECHNOLOGIES IN REVEALING ANTROPOMORPHIC BAS-RELIEFS ON CHUMAKI GROUP OF DOLMENS, GREATER SOCHI - Glazov, Konstantin Anatol'evic; Kudin, Mihail Ivanovic; Kizilov, Andrej Sergeevic (History, Archeology and Ethnography of the Caucasus, 2025)
This article presents the findings of a study on a bas-relief composition adorning the facade slab of a dolmen from the Chumaki dolmen group, situated in the Tsushvadzh River basin within the Lazarevsky district of Greater Sochi. The bas-relief depicts three anthropomorphic figures engaged in a dance. The two flanking figures are depicted in symmetrical, mirror-image poses, with one arm extended toward the central figure and the other bent at the elbow and lowered. The central figure has both arms hanging downward. This compositional motif bears resemblance to the bas-reliefs of the Kapibge-1 dolmen (Greater Sochi) and to the pecked images on the blocks of the dolmen courtyard in the village of Dzhubga. Analysis of the poses of these “twins” reveals parallels with petroglyphs and engravings on dolmens across the Caucasus, as well as with Bronze Age monuments spanning a broad region from Transcaucasia to Crimea – evidence suggesting the persistence of shared mythological narratives in antiquity. This discovery augments the inventory of dolmens in the Greater Sochi region featuring anthropomorphic and geometric motifs executed in bas-relief, potentially indicative of a distinctive stylistic “signature” associated with a local “school.” Identification of the composition was enabled by digital technologies, including photogrammetry and subsequent 3D modeling that leverages shadow and highlight patterns under simulated oblique illumination via gradient procedural textures. Such methods enhance the visibility of bas-relief imagery and uncover poorly preserved elements. In turn, these techniques afford novel opportunities for revealing previously undetected motifs on well-documented monuments.
Keywords: dolmen; historical and cultural heritage; bas-relief petroglyphs; anthropomorphic images; photogrammetry; 3D modelling; Black Sea coast of the Caucasus; Tsuskhvadzh River; Chumaki dolmen group